2018
DOI: 10.1042/bsr20180394
|View full text |Cite
|
Sign up to set email alerts
|

Steroid receptor coactivator-1 interacts with NF-κB to increase VEGFC levels in human thyroid cancer

Abstract: Thyroid cancer is the most common endocrine cancer, and has a high incidence of lymphatic metastasis. Vascular endothelial growth factor C (VEGFC) is essential for development of lymphatic vessels and lymphatic metastases during carcinogenesis. Steroid receptor coactivator-1 (SRC-1) interacts with nuclear receptors and transcription factors to promote tumor proliferation and metastasis. However, the correlation between SRC-1 and VEGFC levels in the lymphatic metastases of thyroid cancer remains unclear. We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In accordance with our study, LYVE1 was previously reported to be downregulated in PTC tumors based on microarrays and this result was confirmed by qPCR and IHC (34). However, Gao et al reported that the expression of steroid receptor coactivator-1 (SRC-1), a potential oncogene, is positively associated with LYVE1 and associated with lymphatic metastasis in PTC (35). Thus, the role of LYVE1 in PTC and its relationship with lymph node metastasis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our study, LYVE1 was previously reported to be downregulated in PTC tumors based on microarrays and this result was confirmed by qPCR and IHC (34). However, Gao et al reported that the expression of steroid receptor coactivator-1 (SRC-1), a potential oncogene, is positively associated with LYVE1 and associated with lymphatic metastasis in PTC (35). Thus, the role of LYVE1 in PTC and its relationship with lymph node metastasis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide evidence for a critical role of SRC‐1 and SRC‐2 in cytokine stimulation of 11β‐HSD1 expression in developing fetal lung. The decline in cytokine signaling in Src‐1/‐2 dKO, in turn, results in decreased NF‐κB activation, which was observed to be mediated by Src‐1/‐2 51,52 …”
Section: Resultsmentioning
confidence: 95%
“…Both SRC‐1 and SRC‐2 increase transcriptional activity of GR 80,81 and its binding to and activation of the C/EBPβ promoter (Figure 3E‐G), whereas, SRC‐1 transcriptionally activates C/EBPα 82 and NF‐κB 51,52 . These glucocorticoid and cytokine regulated pathways, thus, converge on transcriptional activation of C/EBPβ, C/EBPα and NF‐κB.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations